High salinity strongly influences the hydrolysis of hydroxymethyl hydroperoxide on deliquesced aerosol particles with a comparison to cloud droplets - Jia, Y. L.; Chen, Z. M. (Environmental Science & Technology, 2026)
Hydroxymethyl hydroperoxide (HMHP, HOCH2OOH) is one of the most abundant organic peroxides (POs) in the atmosphere. Owing to its extremely high solubility, HMHP readily partitions into cloudwater and aerosol liquid water, where it hydrolyzes to hydrogen peroxide (H2O2) and formaldehyde (HCHO). However, previous studies were conducted in dilute solutions and did not adequately account for the high-salinity characteristic of deliquesced aerosol particles. Here, we systematically investigate the combined effects of pH (0–6), temperature (277–313 K), ionic strength (0–10 M), and ion identity (NH4+, Na+, SO42–, and Cl–) on the hydrolysis kinetics of HMHP. For the first time, a parametrization formula describing the dependence of the hydrolysis rate constant on ionic strength is established, demonstrating that ionic strength exerts only a limited influence on HMHP hydrolysis. However, it is found that in highly concentrated ammonium salt solutions, HMHP undergoes a previously unrecognized NH3-driven reaction pathway. This new pathway competes with hydrolysis, accelerating the apparent transformation rate of HMHP by more than an order of magnitude while significantly reducing the yield of H2O2 and HCHO. Our findings highlight that future atmospheric chemical models should fully account for the NH3-driven pathway in aqueous-phase reactions of POs, thereby enabling a more accurate assessment of the role of POs in atmospheric oxidant cycling and secondary particulate matter formation.